2021
DOI: 10.5653/cerm.2020.04231
|View full text |Cite
|
Sign up to set email alerts
|

The effect of genistein on insulin resistance, inflammatory factors, lipid profile, and histopathologic indices in rats with polycystic ovary syndrome

Abstract: Objective: Polycystic ovary syndrome (PCOS) is characterized by hyperandrogenism, irregular menstruation, ovulatory dysfunction, and insulin resistance. Recent studies have reported the possible role of phytoestrogens in PCOS. This animal study aimed to evaluate the effects of genistein on insulin resistance, inflammatory factors, lipid profile, and histopathologic indices on PCOS. Methods: PCOS was induced by 1 mg/kg of letrozole in adult Sprague-Dawley rats. The rats then received normal saline (PCOS group),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…In vivo study on rats with PCOS treated with soybean isoflavone-aglycone fraction demonstrated decreased IL-6 and TNF-α levels in ovarian tissue ( 25 ). Those findings were comparable with those of Amanat et al ( 45 ), who identified reduced levels of TNF-α in PCOS rat model compared with those in healthy rats. Theca cells, which make androgens, had increased proliferation due to increased TNF-α levels, which also contributed to hyperandrogenism ( 25 ).…”
Section: Effect Of Isoflavone As An Anti-inflammatory Agentsupporting
confidence: 91%
“…In vivo study on rats with PCOS treated with soybean isoflavone-aglycone fraction demonstrated decreased IL-6 and TNF-α levels in ovarian tissue ( 25 ). Those findings were comparable with those of Amanat et al ( 45 ), who identified reduced levels of TNF-α in PCOS rat model compared with those in healthy rats. Theca cells, which make androgens, had increased proliferation due to increased TNF-α levels, which also contributed to hyperandrogenism ( 25 ).…”
Section: Effect Of Isoflavone As An Anti-inflammatory Agentsupporting
confidence: 91%
“…Amanat et al. 99 reported the effects of genistein on IR, inflammatory factors and lipids in rats with polycystic ovary syndrome. Biochemical and histopathological analyses showed that genistein (20 mg/kg/day) significantly alleviated oxidation, inflammation, blood glucose and histopathological indexes in polycystic ovary syndrome rats.…”
Section: Flavonoids: Classification and Biological Propertiesmentioning
confidence: 99%
“…Decreased expression of muscle and adipose GLUT4 in diabetic persons is one of the most important reasons for IR, since it is well known that the absorption of glucose into cells depends on the help of membrane GLUT4. In IR animal models, berberine was found to improve insulin sensitivity by activating AMP-activated protein kinase [ 51 ].…”
Section: Discussionmentioning
confidence: 99%